Older persons in emergencies : an active ageing perspective - World Health Organization (Geneva, Switzerland : World Health Organization, 2008)
In collaboration with the Public Health Agency of Canada and Help the Aged (UK), the World Health Organization commissioned case studies in 2006-2007 to examine how older persons fared in conflict-related and naturally caused emergencies in both developed and developing countries - war, drought, heat wave, floods, hurricanes, earthquakes, tsunami, ice storm, wild fires and a nuclear power plant explosion. The report contributes real-life experiences to inform policy and practice makers about the needs and contributions that older people face during emergency and reconstruction phases.--Publisher's description.
Natural and conflict-related emergencies in an ageing world -- Emergencies and older people : what have we learned? -- Integrating older persons' needs and contributions in emergencies : an active ageing framework -- The policy response -- Conclusion -- Case studies and data sources.
Includes bibliographical references.
Also available online.
Keywords: Emergency Medical Services; Aged; Emergencies; Health Policy; Health Services for the Aged; Older people -- Medical care; Emergency medical services; Health planning; Emergency medical services; Health planning; Older people -- Medical care